Impacts of interactions with low-mineralized water on permeability and pore behavior of carbonate reservoirs - Dmitriy A. Martyushev; Inna N. Ponomareva; Vasiliy I. Chernykh; Shadfar Davoodi; Yousef Kazemzadeh; Tianshou Ma (Energy Geoscience, 2024)
Laboratory filtration experiments are employed to investigate effective well killing while minimizing its impacts on surrounding rocks. The novelty of this experimental study lies in the prolonged exposure of rock samples to the killing fluid for seven days, corresponding to the average duration of well workovers in the oilfields in Perm Krai, Russia. Our findings indicate that critical factors influencing the interactions between rocks and the killing fluid include the chemical composition of the killing fluid, the mineralogical composition of the carbonate rocks, reservoir pressure and temperature, and the contact time. Petrophysical analyses using multi-scale X-ray computed tomography, field emission scanning electron microscopy, and X-ray diffraction were conducted on samples both before and after the well killing simulation. The experiments were performed using real samples of cores, crude oil, and the killing fluid. The results from this study indicate that low-mineralized water (practically fresh water) is a carbonate rock solvent. Such water causes the dissolution of rock components, the formation of new calcite crystals and amoeba-like secretions, and the migration of small particles (clay, quartz, and carbonates). The formation of deep channels was also recorded. The assessment reveals that the change in the pH of the killing fluid indicates that the observed mineral reactions were caused by carbonate dissolution. These combined phenomena led to a decrease in the total number of voids in the core samples, which was 25% on average, predominantly among voids measuring between 45 and 70 μm in size. The change in the pore distribution in the bulk of the samples resulted in decreases in porosity of 1.8% and permeability of 67.0% in the studied core samples. The results from this study indicate the unsuitability of low-mineralized water as a well killing fluid in carbonate reservoirs. The composition of the killing fluid should be optimized, for example, in terms of the ionic composition of water, which we intend to investigate in future research.